Dual-mode dynamic anti-counterfeiting luminescent nano material as well as preparation method and application thereof
By constructing dual-mode dynamic anti-counterfeiting nanomaterials with upconverted fluorescent nanoparticles, silica clad layers and downconverted fluorescent complex Eu(TTA)3 assembly layer, the existing anti-counterfeiting materials lack dynamic luminescence characteristics and poor safety are solved. The problem of this has achieved the improvement of high anti-counterfeiting grade and material properties.
Patent Information
- Application Number
- CN202411350610.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-17
AI Technical Summary
The existing anti-counterfeiting luminescent materials lack dynamic luminescent characteristics, have poor security, and have a low anti-counterfeiting grade.
The dual-mode dynamic anti-counterfeiting nanomaterial consisting of upconverted fluorescent nanoparticles, silica coating and downconverted fluorescent complex Eu(TTA)3 assembly layer was prepared by co-precipitation method and microemulsion method, combined with polysaccharide function The chemical layer improves the chemical stability and biocompatibility of the material.
The dynamic changes in luminous characteristics at different excitation wavelengths and temperatures are achieved, the anti-counterfeiting grade of anti-counterfeiting products is improved, and the chemical stability, light stability and biocompatibility of the materials are enhanced.
Smart Images

Figure CN119144329A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of luminescent materials, and in particular relates to a dual-mode dynamic anti-counterfeiting luminescent nanomaterial and a preparation method and application thereof. Background Art
[0002] At present, the anti-counterfeiting methods for commercially available commodities, stamps, certificates and other products are mainly static anti-counterfeiting methods such as laser holograms, barcodes and watermarks. Static anti-counterfeiting relies on a single anti-counterfeiting mode or is based on static signals, which may be copied. The luminescent properties of some luminescent materials will change when stimulated by external conditions such as different excitation wavelengths, excitation intensities and temperatures. By utilizing the dynamic luminescent properties of such luminescent materials, a more secure dynamic anti-counterfeiting method can be provided.
[0003] Luminescent materials mainly include photoluminescent materials, electroluminescent materials, thermoluminescent materials, and radioluminescent materials; up-conversion luminescent materials in photoluminescent materials have anti-Stokes luminescence characteristics, which can convert long-wavelength, low-energy excitation light into short-wavelength, high-energy emission fluorescence; down-conversion luminescent materials have Stokes luminescence characteristics, which can convert short-wavelength, high-energy excitation light into long-wavelength, low-energy emission fluorescence. In addition to the fluorescence emission characteristics, up-conversion luminescent materials or down-conversion luminescent materials, which are obtained by combining rare earth ions with organic ligands such as 2-thenoyltrifluoroacetone and organic carboxylic acid ligands such as succinic acid, also have the characteristics of higher luminescence efficiency and better luminescence light stability; lanthanide ion doped up-conversion luminescent nanoparticles also have the characteristics of large anti-Stokes shift, narrow emission band, rich emission spectrum, long luminescence lifetime and high light stability. Therefore, up-conversion luminescent materials or down-conversion luminescent materials are good anti-counterfeiting luminescent materials and can be used for anti-counterfeiting of commercial goods, stamps, certificates and other products.
[0004] However, current anti-counterfeiting luminescent materials such as up-conversion luminescent materials or down-conversion luminescent materials are based on single-mode luminescence and do not have dynamic luminescence characteristics. When used for anti-counterfeiting of commercial goods, stamps, certificates and other products, their security and anti-counterfeiting levels need to be improved. Summary of the invention
[0005] In view of this, the present application provides a dual-mode dynamic anti-counterfeiting luminescent nanomaterial and a preparation method and application, which are used to solve the technical problems in the prior art that the anti-counterfeiting luminescent material does not have dynamic luminescent characteristics, has poor security, and has a low anti-counterfeiting level.
[0006] In a first aspect, the present application provides a dual-mode dynamic anti-counterfeiting luminescent nanomaterial, which comprises, from the inside to the outside: up-conversion fluorescent nanoparticles, a silica coating layer, and a down-conversion fluorescent complex Eu(TTA)3 assembly layer;
[0007] The up-conversion fluorescent nanoparticles include, from the inside to the outside, a core nanoparticle NaGdF4:Yb / Tm, a NaYF4:Tb inner shell layer and a NaYF4 outer shell layer.
[0008] Preferably, in the core nanoparticle NaGdF4:Yb / Tm of the upconversion fluorescent nanoparticles, the molar ratio of Yb: Tm: Gd is 40~80:0.5~2:20~60, and in the NaYF4:Tb inner shell, the molar ratio of Y: Tb is 70~95:5~30.
[0009] Preferably, in the dual-mode dynamic anti-counterfeiting luminescent nanomaterial, the particle size of the upconversion fluorescent nanoparticles is 15-80 nm, and the thickness of the silica coating layer is 1-5 nm.
[0010] Preferably, in the upconversion fluorescent nanoparticles, the thickness of the core nanoparticle NaGdF4:Yb / Tm is 10-60 nm, the thickness of the inner shell layer of NaYF4:Tb is 2.5-10 nm, and the thickness of the outer shell layer of NaYF4 is 2.5-10 nm.
[0011] Preferably, the molar ratio of the up-conversion fluorescent nanoparticles to the down-conversion fluorescent complex Eu(TTA)3 assembly layer is 2.5:1.
[0012] Preferably, the dual-mode dynamic anti-counterfeiting luminescent nanomaterial further comprises a polysaccharide functionalized layer, and the polysaccharide functionalized layer is bonded to the surface of the down-conversion fluorescent complex Eu(TTA)3 assembly layer through electrostatic action.
[0013] Preferably, the polysaccharide functionalized layer is selected from a hyaluronic acid functionalized layer and / or a chitosan functionalized layer.
[0014] Preferably, in the dual-mode dynamic anti-counterfeiting luminescent nanomaterial, the ratio of the upconversion fluorescent nanoparticles to the hyaluronic acid functionalized layer is 0.01 mol:0.04 g;
[0015] The ratio of the up-conversion fluorescent nanoparticles to the chitosan functional layer is 0.01 mol:0.3 g.
[0016] The second aspect of the present application provides a method for preparing a dual-mode dynamic anti-counterfeiting luminescent nanomaterial, which can prepare the dual-mode dynamic anti-counterfeiting luminescent nanomaterial described in the first aspect. The preparation method comprises the following steps:
[0017] Step S1, adding ammonium fluoride and sodium hydroxide to a precursor reaction solution containing a gadolinium / ytterbium / thulium-oleic acid complex to carry out a core coprecipitation reaction to obtain core nanoparticles NaGdF4:Yb / Tm;
[0018] Step S2, adding core nanoparticles NaGdF4:Yb / Tm, ammonium fluoride and sodium hydroxide to a precursor reaction solution containing yttrium / terbium-oleic acid complex to carry out inner shell coprecipitation reaction to obtain core-shell nanoparticles NaGdF4:Yb / Tm@NaYF4:Tb;
[0019] Step S3, adding NaGdF4:Yb / Tm@NaYF4:Tb, ammonium fluoride and sodium hydroxide to the precursor reaction solution containing yttrium-oleic acid complex to carry out shell layer co-precipitation reaction to obtain up-conversion fluorescent nanoparticles NaGdF4:Yb / Tm@NaYF4:Tb@NaYF4;
[0020] Step S4, using a microemulsion method to coat the surface of NaGdF4:Yb / Tm@NaYF4:Tb@NaYF4 with a silicon dioxide modified layer to obtain UCNPs@SiO2;
[0021] Step S5, UCNPs@SiO2, europium salt, 2-thenoyltrifluoroacetone, and ammonia water are subjected to coordination reaction in an ethanol solution, and a fluorescent complex Eu(TTA)3 assembly layer is converted on the surface of UCNPs@SiO2 to obtain UCNPs@SiO2-Eu(TTA)3.
[0022] Preferably, in step S4, coating the surface of NaGdF4:Yb / Tm@NaYF4:Tb@NaYF4 with a silicon dioxide modification layer by a microemulsion method specifically comprises:
[0023] Step S41, mixing NaGdF4:Yb / Tm@NaYF4:Tb@NaYF4, a surfactant, and an alkali solution, and stirring to obtain an alkaline water-in-oil emulsion;
[0024] Step S42, adding tetraethyl orthosilicate into an alkaline water-in-oil emulsion for hydrolysis, and coating the surface of NaGdF4:Yb / Tm@NaYF4:Tb@NaYF4 with a silicon dioxide modification layer.
[0025] Step S43, centrifuging and washing in sequence to obtain UCNPs@SiO2.
[0026] Preferably, in step S5, UCNPs@SiO2, europium salt, 2-thenoyltrifluoroacetone, and ammonia water are subjected to coordination reaction in an ethanol solution, and the surface of UCNPs@SiO2 is coated with a down-conversion fluorescent complex Eu(TTA)3 assembly layer to obtain UCNPs@SiO2-Eu(TTA)3, which specifically includes:
[0027] Step S51, adding the ethanol solution of europium salt to the ethanol solution of UCNPs@SiO2, and sequentially subjecting to ultrasonication, rotation vibration, and centrifugation to obtain UCNPs@SiO2-Eu;
[0028] Step S52: Add the ethanol solution of 2-thenoyltrifluoroacetone and ammonia water to the ethanol solution of UCNPs@SiO2-Eu to carry out coordination reaction to obtain UCNPs@SiO2-Eu(TTA)3.
[0029] Preferably, after step S5, the method further comprises the following steps:
[0030] Step S6, modifying hyaluronic acid onto the surface of UCNPs@SiO2-Eu(TTA)3 through electrostatic interaction to obtain UCNPs@SiO2-Eu(TTA)3-HYA;
[0031] Step S7, modifying chitosan onto the surface of UCNPs@SiO2-Eu(TTA)3-HYA through electrostatic interaction to obtain UCNPs@SiO2-Eu(TTA)3-HYA / CS.
[0032] Preferably, in step S1, the method for preparing the precursor reaction solution of the gadolinium / ytterbium / thulium-oleic acid complex comprises: conducting a coordination reaction of gadolinium salt, ytterbium salt, thulium salt, oleic acid and 1-octadecene to prepare the precursor reaction solution of the gadolinium / ytterbium / thulium-oleic acid complex;
[0033] In step S2, the method for preparing the precursor reaction liquid of the yttrium / terbium-oleic acid complex comprises: conducting a coordination reaction between yttrium salt, terbium salt, oleic acid and 1-octadecene to prepare the precursor reaction liquid of the yttrium / terbium-oleic acid complex;
[0034] In step S3, the method for preparing the precursor reaction solution of the yttrium-oleic acid complex comprises: conducting a coordination reaction between yttrium salt, oleic acid and 1-octadecene to prepare the precursor reaction solution of the yttrium-oleic acid complex.
[0035] Preferably, in step S1 to step S3, the coordination reaction is carried out at a temperature of 150 to 180° C. and for a time of 20 to 40 min.
[0036] Preferably, in step S1 to step S3, the process of the core coprecipitation reaction, the inner shell coprecipitation reaction, and the outer shell coprecipitation reaction is: heating to 50°C for 30 minutes, heating to 110°C for 25 minutes, removing methanol, evacuating for 10 minutes, then heating to 300°C, and reacting under argon atmosphere for 1 hour.
[0037] The fourth aspect of the present application provides the use of the dual-mode dynamic anti-counterfeiting luminescent nanomaterial described in the first aspect in the preparation of anti-counterfeiting products or information storage.
[0038] The fourth aspect of the present application provides a security ink, the components of which include: the dual-mode dynamic anti-counterfeiting luminescent nanomaterial described in the first aspect.
[0039] The fifth aspect of the present application provides an anti-counterfeiting product, comprising a product and a dual-mode dynamic anti-counterfeiting luminescent nanomaterial as described in the first aspect;
[0040] The dual-mode dynamic anti-counterfeiting luminescent nanomaterial covers the surface of the product.
[0041] In summary, the present application provides a dual-mode dynamic anti-counterfeiting luminescent nanomaterial, a preparation method and an application. The present application provides a dual-mode dynamic anti-counterfeiting luminescent nanomaterial. The components of the dual-mode dynamic anti-counterfeiting luminescent nanomaterial from the inside to the outside include: up-conversion fluorescent nanoparticles, a silica coating layer, and a down-conversion fluorescent complex Eu(TTA)3 assembly layer. The up-conversion fluorescent nanoparticles are specifically core nanoparticles NaGdF4:Yb / Tm, NaYF4:Tb inner shell layer and NaYF4 outer shell layer from the inside to the outside; under the excitation of different excitation wavelengths and the action of temperature, the luminescence characteristics of the dual-mode dynamic anti-counterfeiting luminescent nanomaterial provided by the present application can be changed, and it has dynamic luminescence characteristics; at the same time, the setting of the silica coating layer and the polysaccharide functionalized layer also improves the chemical stability, photostability, hydrophilicity, water dispersibility, biocompatibility and other properties of the dual-mode dynamic anti-counterfeiting luminescent nanomaterial, thereby solving the technical problems in the prior art that the anti-counterfeiting luminescent materials do not have dynamic luminescence characteristics, poor security, and low anti-counterfeiting level. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0043] Figure 1 Electron micrographs of the core nanoparticles provided in Example 1 of the present application, the core nanoparticles coated with the inner shell layer, the upconversion fluorescent nanoparticles, and the nanoparticles coated with silica;
[0044] Figure 2 Infrared spectra of upconversion fluorescent nanoparticles provided in Example 1 of the present application, upconversion fluorescent nanoparticles coated with silica, upconversion fluorescent nanoparticles coated with an assembly layer of a downconversion fluorescent complex Eu(TTA)3, upconversion fluorescent nanoparticles coated with hyaluronic acid (HYA), and upconversion fluorescent nanoparticles coated with hyaluronic acid and chitosan (HYA / CS);
[0045] Figure 3X-ray diffraction patterns and zeta potential patterns of the upconversion fluorescent nanoparticles provided in Example 1 of the present application, the upconversion fluorescent nanoparticles coated with silica, the upconversion fluorescent nanoparticles coated with the assembly layer of the downconversion fluorescent complex Eu(TTA)3, the upconversion fluorescent nanoparticles coated with hyaluronic acid (HYA), and the upconversion fluorescent nanoparticles coated with hyaluronic acid and chitosan (HYA / CS);
[0046] Figure 4 A graph showing the water contact angle test results of UCNPs-OA and UCNPs@SiO2 provided in Example 1 of the present application;
[0047] Figure 5 The up-conversion emission spectrum of UCNPs-OA and the down-conversion emission spectrum of Eu(TTA)3 in a dual-mode dynamic anti-counterfeiting luminescent nanomaterial provided in Example 1 of the present application;
[0048] Figure 6 In a dual-mode dynamic anti-counterfeiting luminescent nanomaterial provided in Example 1 of the present application, the up-conversion emission spectra of UCNPs@SiO2, UCNPs@SiO2-Eu(TTA)3, UCNPs@SiO2-Eu(TTA)3-HYA, UCNPs@SiO2-Eu(TTA)3-HYA / CS and the down-conversion emission spectra of UCNPs@SiO2-Eu(TTA)3;
[0049] Figure 7 In a dual-mode dynamic anti-counterfeiting luminescent nanomaterial provided in Example 1 of the present application, the up-conversion emission spectrum of UCNPs-OA (300K~500K) and the down-conversion emission spectrum of Eu(TTA)3 (77K~350K);
[0050] Figure 8 In a dual-mode dynamic anti-counterfeiting luminescent nanomaterial provided in Example 1 of the present application, an up-conversion emission fluorescence image of UCNPs-OA at 300K and 500K and a down-conversion emission fluorescence image of Eu(TTA)3 at 300K and 350K;
[0051] Fig. 9 An anti-counterfeiting product prepared with a dual-mode dynamic anti-counterfeiting luminescent nanomaterial provided in Example 1 of the present application shows emission fluorescence images under excitation with 365nm ultraviolet light / 980nm near-infrared light at room temperature, 350K and 500K respectively. DETAILED DESCRIPTION
[0052] The present application provides a dual-mode dynamic anti-counterfeiting luminescent nanomaterial, a preparation method and an application thereof, which are used to solve the technical problems in the prior art that the anti-counterfeiting luminescent material does not have dynamic luminescent characteristics, has poor security and a low anti-counterfeiting level.
[0053] The technical solution of the present application will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0054] In view of the fact that current luminescent materials are usually based on single-mode luminescence, do not have dynamic luminescence characteristics, have poor security, and have low anti-counterfeiting levels, the present application provides a dual-mode dynamic anti-counterfeiting luminescent nanomaterial. The components of the dual-mode dynamic anti-counterfeiting luminescent nanomaterial from the inside to the outside include: up-conversion fluorescent nanoparticles, a silica coating layer, and a down-conversion fluorescent complex Eu(TTA)3 assembly layer. The up-conversion fluorescent nanoparticles are specifically core nanoparticles NaGdF4:Yb / Tm, a NaYF4:Tb inner shell layer, and a NaYF4 outer shell layer from the inside to the outside; the up-conversion fluorescent nanoparticles in the dual-mode dynamic anti-counterfeiting luminescent nanomaterial can be excited by low-energy 980nm near-infrared excitation light to produce high-energy up-conversion emission fluorescence, and the wavelength range of the up-conversion emission fluorescence is in the ultraviolet-visible light region. At the same time, the down-conversion fluorescent complex Eu(TTA)3 assembly layer in the dual-mode dynamic anti-counterfeiting luminescent nanomaterial can be excited by high-energy 365nm ultraviolet light to produce low-energy down The wavelength range of the up-conversion emission fluorescence and the down-conversion emission fluorescence is in the visible light region; wherein, after being excited by light of different wavelengths, the fluorescence colors of the up-conversion emission fluorescence and the down-conversion emission fluorescence are different, and the luminescent nanomaterial has a dual-mode luminescence characteristic; and when the temperature changes, for example, when the temperature changes from 300K to 500K, the fluorescence intensities of the up-conversion emission fluorescence and the down-conversion emission fluorescence are different, and the luminescent nanomaterial has a dynamic luminescence characteristic, so that the dual-mode dynamic anti-counterfeiting luminescent nanomaterial provided in the present application can change its luminescence characteristics under different excitation wavelengths and temperatures, has a dual-mode dynamic luminescence characteristic, and the prepared anti-counterfeiting product has a higher anti-counterfeiting level; and the silica coating layer in the dual-mode dynamic anti-counterfeiting luminescent nanomaterial can further improve the chemical stability, photostability, hydrophilicity, water dispersibility and other properties of the dual-mode dynamic anti-counterfeiting luminescent nanomaterial; thereby overcoming the defects that the current luminescent materials are usually based on single-mode luminescence, do not have dynamic luminescence characteristics, have poor security, and have a low anti-counterfeiting level.
[0055] Preferably, in order to improve the biocompatibility and other properties of the dual-mode dynamic anti-counterfeiting luminescent nanomaterial, the dual-mode dynamic anti-counterfeiting luminescent nanomaterial provided in the present application also includes a polysaccharide functionalized layer, and the polysaccharide functionalized layer is bonded to the outermost layer of the dual-mode dynamic anti-counterfeiting luminescent nanomaterial through electrostatic action. The characteristics of the polysaccharide can be utilized to improve the biocompatibility, hydrophilicity and other properties of the dual-mode dynamic anti-counterfeiting luminescent nanomaterial. This makes the dual-mode dynamic anti-counterfeiting luminescent nanomaterial can be used to prepare anti-counterfeiting products for tableware and medical devices with higher safety requirements.
[0056] Preferably, for the composition of the polysaccharide functionalized layer in a dual-mode dynamic anti-counterfeiting luminescent nanomaterial provided in the present application, the polysaccharide is selected from hyaluronic acid and / or chitosan; and the amount used is 0.04g of hyaluronic acid and / or 0.3g of chitosan per 0.01 mol of up-conversion fluorescent nanoparticles.
[0057] At the same time, the present application also provides a method for preparing a dual-mode dynamic anti-counterfeiting luminescent nanomaterial, the preparation method including co-precipitation to prepare upconversion fluorescent nanoparticles, microemulsion method to coat silica, coordination reaction to prepare Eu(TTA)3 assembly layer, and electrostatic action to combine polysaccharide functionalized layer.
[0058] In the preparation method, upconversion fluorescent nanoparticles are prepared by coprecipitation method, firstly, a rare earth-oleic acid complex solution is prepared, and then ammonium fluoride, sodium hydroxide and the rare earth-oleic acid complex are subjected to coprecipitation reaction, so that core nanoparticles NaGdF4:Yb / Tm, NaYF4:Tb inner shell layer and NaYF4 outer shell layer can be prepared in sequence; during the preparation process, the core nanoparticles NaGdF4:Yb / Tm and other products can be stored in a cyclohexane solution;
[0059] The microemulsion method is used to coat silica in order to utilize the alkaline environment provided by ammonia water to promote the hydrolysis of tetraethyl orthosilicate, and to coat silica on the surface of the upconversion fluorescent nanoparticles; after coating silica, a coordination reaction is performed to prepare the Eu(TTA)3 assembly layer, and then the electrostatic interaction between positive and negative charges is utilized to bind hyaluronic acid and / or chitosan to the surface of the Eu(TTA)3 assembly layer.
[0060] The application of a dual-mode dynamic anti-counterfeiting luminescent nanomaterial provided in this application can be used to prepare security ink; current security inks are mainly used for products such as banknotes, checks, stamps, passports, etc., which can prevent counterfeiting by commercial offset printing machines and other equipment. The security ink used in this application is a luminescent security ink, which, when covered on the surface of the product, can produce fluorescence of different colors / intensities under near-infrared / ultraviolet light excitation.
[0061] Furthermore, the present application also provides an anti-counterfeiting product, which includes a product and a surface-covered dual-mode dynamic anti-counterfeiting luminescent nanomaterial provided by the present application; as for the types of products, they can be tableware, medical devices and other products.
[0062] Accordingly, the process of the authenticity identification method of the anti-counterfeiting product provided in this application includes:
[0063] The anti-counterfeiting product is irradiated with an excitation light of 365 nm or 980 nm so that the anti-counterfeiting product emits fluorescence, and the authenticity of the anti-counterfeiting product is identified according to the color of the emitted fluorescence;
[0064] Or the anti-counterfeiting product is heated to 300K-500K, and irradiated with 365nm or 980nm excitation light to make the anti-counterfeiting product emit fluorescence, and the authenticity of the anti-counterfeiting product is identified according to the color and intensity of the emitted fluorescence.
[0065] Furthermore, the present application also provides an application of a dual-mode dynamic anti-counterfeiting luminescent nanomaterial in the preparation of anti-counterfeiting products or information storage; since the dual-mode dynamic anti-counterfeiting luminescent nanomaterial provided by the present application has dynamic luminescent characteristics, it can be used for information storage in addition to the anti-counterfeiting field.
[0066] The following will specifically describe a dual-mode dynamic anti-counterfeiting luminescent nanomaterial provided by the present application in combination with embodiments and experimental examples.
[0067] Example 1
[0068] Example 1 of the present application provides a method for preparing a dual-mode dynamic anti-counterfeiting luminescent nanomaterial, the preparation method comprising the steps of preparing upconversion fluorescent nanoparticles by co-precipitation, coating silica by microemulsion method, preparing a Eu(TTA)3 assembly layer by coordination reaction, and modifying a polysaccharide functionalized layer.
[0069] The steps of preparing up-conversion fluorescent nanoparticles by coprecipitation include: preparing a precursor reaction liquid of a rare earth-oleic acid complex, performing a coprecipitation reaction, and storing the mixture in a cyclohexane dispersion.
[0070] The process of preparing the precursor reaction solution of the rare earth-oleic acid complex includes:
[0071] Gadolinium acetate (0.2 mmol), ytterbium acetate (0.196 mmol), thulium acetate (0.004 mmol), oleic acid (4 mL) and 1-octadecene (6 mL) were added into a two-necked flask; the mixture was heated to 160° C. in a heating mantle and reacted for 30 min, water in the reaction system was removed, and the mixture was cooled to room temperature to obtain a precursor reaction solution containing a gadolinium / ytterbium / thulium-oleic acid complex;
[0072] Yttrium acetate (0.36 mmol), terbium acetate (0.04 mmol), oleic acid (4 mL) and 1-octadecene (6 mL) were added into a two-necked flask; the mixture was heated to 160° C. in a heating mantle and reacted for 30 min, water in the reaction system was removed, and the mixture was cooled to room temperature to obtain a precursor reaction solution containing yttrium / terbium-oleic acid complex;
[0073] Yttrium acetate (0.4 mmol), oleic acid (4 mL) and 1-octadecene (6 mL) were added to a two-necked flask; the mixture was heated to 160° C. in a heating mantle and reacted for 30 min, water in the reaction system was removed, and the mixture was cooled to room temperature to obtain a precursor reaction solution containing a yttrium / -oleic acid complex.
[0074] The process of the nuclear co-precipitation reaction includes: adding NH4F (1.52 mmol) and NaOH (1 mmol) to the precursor reaction solution containing gadolinium / ytterbium / thulium-oleic acid complex, heating the mixed solution to 50°C for reaction for 30 minutes; heating to 110°C for reaction for 25 minutes, and removing methanol; vacuuming for 10 minutes and then heating to 300°C, reacting for 1 hour under argon atmosphere to obtain oleic acid-coated core nanoparticles NaGdF4:Yb / Tm (Gd:Yb:Tm=50mol%:49mol%:1mol%).
[0075] The process of preparing the cyclohexane dispersion includes: cooling to room temperature after the reaction is completed, transferring the oleic acid-coated core nanoparticle reaction liquid to a centrifuge tube, adding anhydrous ethanol (4 mL, 99.5%), suspending and shaking evenly, centrifuging at 7500 rpm for 6 minutes, and removing the upper liquid; adding cyclohexane (4 mL, 99.5%), adding anhydrous ethanol (8 mL, 99.5%), suspending and shaking evenly, centrifuging at 7500 rpm for 6 minutes, and removing the upper liquid; adding cyclohexane (4 mL, 99.5%), anhydrous ethanol (4 mL, 99.5%), and methanol (4 mL, 99.5%), suspending and shaking evenly, centrifuging at 7500 rpm for 6 minutes, and removing the upper liquid to obtain oleic acid-coated core nanoparticles; dispersing it in cyclohexane (4 mL, 99.5%), sealing and storing at low temperature, and obtaining oleic acid-coated core nanoparticles NaGdF4:Yb / Tm cyclohexane dispersion.
[0076] The process of inner-shell coprecipitation reaction includes: adding core nanoparticle NaGdF4:Yb / Tm cyclohexane dispersion (3.9 mL), NH4F (1.52 mmol) and NaOH (1 mmol) to a precursor reaction solution containing yttrium / terbium-oleic acid complex, heating to 50°C for reaction for 30 minutes; heating to 110°C for reaction for 25 minutes, and removing methanol; vacuuming for 10 minutes and then heating to 300°C, reacting for 1 hour under argon atmosphere to obtain oleic acid-coated core-shell structured nanoparticles, whose composition is NaGdF4:Yb / Tm@NaYF4:Tb (Gd:Yb:Tm=50mol%:49mol%:1mol%, Y:Tb=90mol%:10mol%).
[0077] The process of preparing the cyclohexane dispersion includes: transferring the reaction solution of oleic acid-coated core-shell structured nanoparticles NaGdF4:Yb / Tm@NaYF4:Tb into a centrifuge tube, adding anhydrous ethanol (4 mL, 99.5%), suspending and shaking evenly, centrifuging at 7500 rpm for 6 minutes, and removing the upper liquid; adding cyclohexane (4 mL, 99.5%) and anhydrous ethanol (8 mL, 99.5%), suspending and shaking evenly, centrifuging at 7500 rpm for 6 minutes, and removing the upper liquid; adding cyclohexane (4 mL, 99.5%), anhydrous ethanol (4 mL, 99.5%), methanol (4 mL, 99.5%), suspending and shaking evenly, centrifuging at 7500 rpm for 6 minutes, and removing the upper liquid to obtain oleic acid-coated core-shell structured nanoparticles; dispersing them in cyclohexane (3.9 mL, 99.5%) to prepare NaGdF4:Yb / Tm@NaYF4:Tb cyclohexane dispersion.
[0078] The process of the outer shell co-precipitation reaction includes: adding NaGdF4:Yb / Tm@NaYF4:Tb cyclohexane dispersion (3.8 mL), NH4F (1.52 mmol) and NaOH (1 mmol) to the precursor reaction solution containing rare earth-oleic acid complex; heating the mixed solution to 50°C for reaction for 30 minutes; heating to 110°C for reaction for 25 minutes, and removing methanol; vacuuming for 10 minutes and then heating to 300°C, and then reacting for 1 hour under an argon atmosphere to obtain oleic acid-coated core-shell-shell structured upconversion fluorescent nanoparticles NaGdF4:Yb / Tm@NaYF4:Tb@NaYF4; (Gd:Yb:Tm=50mol%:49mol%:1mol%, Y:Tb=90mol%:10mol%)@NaYF4, abbreviated as core-shell-shell structured UCNPs-OA.
[0079] The process of preparing the cyclohexane dispersion includes: transferring the UCNPs-OA reaction solution to a centrifuge tube, adding anhydrous ethanol (4 mL, 99.5%), suspending and shaking evenly, centrifuging at 7500 rpm for 6 min, and removing the upper liquid; adding cyclohexane (4 mL, 99.5%) and anhydrous ethanol (8 mL, 99.5%), suspending and shaking evenly, centrifuging at 7500 rpm for 6 min, and removing the upper liquid; adding cyclohexane (4 mL, 99.5%), anhydrous ethanol (4 mL, 99.5%), and methanol (4 mL, 99.5%), suspending and shaking evenly, centrifuging at 7500 rpm for 6 min, and removing the upper liquid; dispersing the obtained UCNPs-OA in cyclohexane (3.8 mL, 99.5%) to prepare an OA-UCNPs cyclohexane dispersion.
[0080] The steps of coating silica by microemulsion method include:
[0081] Add 10 mL of cyclohexane to the OA-UCNPs cyclohexane dispersion (0.7 mL), shake evenly, add 0.4 g of surfactant CO-520, and stir for 10 min. Then, add 1.6 g of CO-520 and 80 μL of ammonia water (28%-30%) in sequence to form an alkaline oil-in-water microemulsion, and sonicate for 30 minutes.
[0082] 40 μL of tetraethyl silicate (TEOS) was slowly added and stirred for 48 h to hydrolyze to form a silica coating.
[0083] The particles were washed twice with ethanol and centrifuged at 15000 rpm for 15 min. The particles (UCNPs@SiO2) were collected and dispersed in 7 mL of ethanol to obtain an ethanol solution of UCNPs@SiO2 (0.01 mmol / mL).
[0084] The steps of preparing the Eu(TTA)3 assembly layer by coordination reaction include:
[0085] Take 3 mL of UCNPs@SiO2 ethanol solution in a centrifuge tube, add 1.2 mL of europium salt ethanol solution (10 mM), ultrasonicate for 1 h at room temperature, and vibrate for 24 h; centrifuge at 16000 rpm for 20 min, collect the lower layer of nanoparticles, and obtain UCNPs@SiO2-Eu;
[0086] Re-disperse UCNPs@SiO2-Eu in ethanol (3 mL), continue to add 1.2 mL of 2-thenoyltrifluoroacetone (TTA) ethanol solution (30 mM), ultrasonically disperse, then add 75 μL of ammonia water (28%-30%), rotate for 24 hours; centrifuge at 16000 rpm for 20 minutes, collect the lower layer of nanocomposite UCNPs@SiO2-Eu(TTA)3, wash with ethanol, and disperse in 3 mL of ethanol (0.01 mmol / mL) to obtain.
[0087] At the same time, the present embodiment also uses 1.2mL of ethanol solution of europium salt (10mM), 1.2mL of ethanol solution of 2-thenoyltrifluoroacetone (TTA) (30mM) and 75μL of ammonia water (28%-30%) to prepare Eu(TTA)3 for testing its down-conversion luminescence performance.
[0088] The steps of modifying the polysaccharide functional layer include: adding 0.04 mL of hyaluronic acid HYA (1 mg / mL) to 1 mL of UCNPs@SiO2-Eu(TTA)3 (0.01 mmol / mL), stirring at room temperature for 20 minutes, and the polyanion HYA containing functional groups such as carboxyl and hydroxyl groups is coated on the surface of the positively charged Eu(TTA)3 complex through electrostatic action to prepare UCNPs@SiO2-Eu(TTA)3-HYA solution; continuing to add 0.3 mL of positively charged polycationic chitosan CS (1 mg / mL), stirring at room temperature for 20 minutes, and CS is coated on the negatively charged surface of UCNPs@SiO2-Eu(TTA)3-HYA through electrostatic action to obtain the dual-mode dynamic anti-counterfeiting luminescent nanomaterial UCNPs@SiO2-Eu(TTA)3-HYA / CS.
[0089] At the same time, this example also continued to prepare a dual-mode dynamic anti-counterfeiting luminescent nanomaterial UCNPs@SiO2-Eu(TTA)3-HYA / CS with a CS dosage of 0.4 mL.
[0090] Experimental Example 1
[0091] Experimental Example 1 of the present application conducted structural and performance tests on NaGdF4:Yb / Tm, NaGdF4:Yb / Tm@NaYF4:Tb, NaGdF4:Yb / Tm@NaYF4:Tb@NaYF4, UCNPs-OA, UCNPs@SiO2, UCNPs@SiO2-Eu(TTA)3, UCNPs@SiO2-Eu(TTA)3-HYA, and UCNPs@SiO2-Eu(TTA)3-HYA / CS prepared by the preparation method provided in Example 1.
[0092] The instruments used for structure and performance testing include: Japanese HT7700 transmission electron microscope, working voltage is 100kV; X-ray diffractometer (XRD, Malvern Panalytical DY 735, UK), scanning rate is 5min -1 , 2θ range of 10-90°; American Thermo-Filsher-Nicolet 6700 Fourier transform infrared spectrometer, scanning range of 4000~400cm -1, resolution 2cm -1 , scanning number 32; British Zeta potential analyzer (Malvern, UK) was used to measure the Zeta potential of liquid samples, and contact angle tester was used to test the water contact angle of samples.
[0093] The electron microscope images of the core nanoparticles NaGdF4:Yb / Tm, NaGdF4:Yb / Tm@NaYF4:Tb, upconversion luminescent nanoparticles NaGdF4:Yb / Tm@NaYF4:Tb@NaYF4, and UCNPs@SiO2 prepared by the preparation method provided in Example 1 are as follows: Figure 1 As shown in the a~d figure; from Figure 1 It can be seen that the upconversion luminescent nanoparticles prepared by the preparation method provided in the present application are of nanometer size. The specific size is that the diameter of the core nanoparticle NaGdF4:Yb / Tm is 14.7nm, the diameter after coating with the NaYF4:Tb inner shell layer is 22.2nm, the diameter after coating with the NaYF4 outer shell layer is 29.5nm, and the diameter after coating with SiO2 is 32.7nm.
[0094] During the preparation process provided in Example 1, the infrared spectra of UCNPs-OA, UCNPs@SiO2, UCNPs@SiO2-Eu(TTA)3, UCNPs@SiO2-Eu(TTA)3-HYA coated with a polysaccharide functional layer, and UCNPs@SiO2-Eu(TTA)3-HYA / CS are shown in FIG. Figure 2 As shown in Figure a~b; Figure 2 It can be seen that compared with UCNPs-OA, UCNPs@SiO2 has a -1 and 798cm -1 The characteristic peak of Si-O-Si appears near 959cm -1 The characteristic peak of Si-OH appears near 463cm -1 The characteristic peak of Si-O appears near 1589cm -1 The carbonyl asymmetric stretching vibration peak appears near UCNPs@SiO2-Eu(TTA)3; compared with UCNPs@SiO2-Eu(TTA)3, UCNPs@SiO2-Eu(TTA)3-HYA has a peak at 1629cm -1 The characteristic peak of carboxyl group appears near 1595 cm -1 The carbonyl characteristic peak appeared near 1084 cm-1, and the CO characteristic peak appeared near 1631 cm-1 of UCNPs@SiO2-Eu(TTA)3-HYA / CS. -1The intensity of the NH characteristic peak nearby is enhanced; it can be seen from the characteristic peaks that the preparation method provided in Example 1 successfully prepared products such as UCNPs-OA, UCNPs@SiO2, UCNPs@SiO2-Eu(TTA)3, UCNPs@SiO2-Eu(TTA)3-HYA coated with a polysaccharide functional layer, and UCNPs@SiO2-Eu(TTA)3-HYA / CS.
[0095] At the same time, during the preparation process provided in Example 1, the product can also be characterized by X-ray diffraction and zeta potential; wherein the X-ray diffraction patterns of UCNPs-OA and UCNPs@SiO2 are as follows Figure 3 As shown in Figure a~b; Figure 3 As can be seen from Figure a, the diffraction peaks of UCNPs-OA and UCNPs@SiO2 match well with the standard card of β-NaYF4 (JCPDS No. 16-0334), UCNPs-OA and UCNPs@SiO2 are pure hexagonal crystal phase structures, and the surface coating modification of silica has little effect on the crystal structure of UCNPs;
[0096] UCNPs@SiO2, UCNPs@SiO2-Eu(TTA)3, UCNPs@SiO2-Eu(TTA)3-HYA 0.04 、UCNPs@SiO2-Eu(TTA)3-HYA 0.04 / CS 0.3 、UCNPs@SiO2-Eu(TTA)3-HYA 0.04 / CS 0.4 The zeta potential diagram is as follows Figure 3 As shown in Figure b, the Zeta potential of UCNPs@SiO2 is negative, about -20 mV, while the Zeta potential of UCNPs@SiO2-Eu(TTA)3 combined with Eu(TTA)3 is about -12 mV, and the Zeta potential of UCNPs@SiO2-Eu(TTA)3-HYA combined with hyaluronic acid (HYA) moves to a negative potential of about -18 mV, while the Zeta potential of UCNPs@SiO2-Eu(TTA)3-HYA combined with chitosan (CS) is about -18 mV. YA / CS, its Zeta potential value moves toward the positive potential, about 6mV, and the amount of chitosan (CS) is increased to 0.4mL, and its Zeta potential value is increased to about 15mV; therefore, in the preparation process of the dual-mode dynamic anti-counterfeiting luminescent nanomaterial provided in Example 1, the amount of raw materials such as hyaluronic acid and chitosan can be increased or decreased as needed to control the ratio of positive and negative charges to regulate the aggregation of the hybrid nanostructure and control its morphology; the dual-mode dynamic anti-counterfeiting luminescent nanomaterial can be widely used in security inks, anti-counterfeiting and information storage and other fields.
[0097] At the same time, during the preparation process provided in Example 1, the present application also tested the water contact angle of the upconversion fluorescent nanoparticles before and after silica coating. The water contact angles of UCNPs-OA and UCNPs@SiO2 are as follows: Figure 4 As shown in Figure a~b; Figure 4 It can be seen that silica coating can improve the hydrophilicity, water dispersibility and other properties of upconversion fluorescent nanoparticles. At the same time, silica coating also enhances the chemical stability and photostability of the upconversion fluorescent nanoparticles. Combined with the previous X-ray diffraction test results, it can be seen that silica coating does not change the crystal structure of the upconversion fluorescent nanoparticles.
[0098] Experimental Example 2
[0099] Experimental Example 2 of the present application tests the luminescence performance of UCNPs-OA, UCNPs@SiO2, UCNPs@SiO2-Eu(TTA)3, UCNPs@SiO2-Eu(TTA)3-HYA, and UCNPs@SiO2-Eu(TTA)3-HYA / CS prepared by the preparation method provided in Example 1; the instruments used in the luminescence performance test include: Ocean Optics USB-2000+ fluorescence spectrometer, with a 980nm near-infrared semiconductor laser as the excitation light source; American HORIBA Jobin Yvon Fluoromax fluorescence spectrometer, with a xenon lamp as the excitation light source; using a near-infrared semiconductor laser as the excitation light source, using a Horiba Jobin Yvon LabRAM HREvolution micro-confocal Raman spectrometer to measure the up-conversion fluorescence emission spectrum in the temperature range of 300-500 K; using a xenon lamp as the excitation light source, using a Horiba Jobin Yvon Fluorolog-3 fluorescence spectrometer to measure the down-conversion fluorescence emission spectrum in the temperature range of 77-350 K.
[0100] Among them, in a dual-mode dynamic anti-counterfeiting luminescent nanomaterial provided in Example 1, the up-conversion luminescence spectrum of UCNPs-OA and the down-conversion emission spectrum of Eu(TTA)3 under the excitation of 980nm diode laser / 365nm xenon lamp as the excitation light source are as follows: Figure 5 As shown in Figure a~b; Figure 5It can be seen that under the excitation of a 980nm diode laser as an excitation light source, the UCNPs-OA in the dual-mode dynamic anti-counterfeiting luminescent nanomaterial has multiple up-conversion characteristic emission peaks in the wavelength range of 311nm~695nm, while Eu(TTA)3 has multiple down-conversion characteristic emission peaks in the wavelength range of 500nm~750nm under the excitation of a 365nm xenon lamp as an excitation light source. This shows that the dual-mode dynamic anti-counterfeiting luminescent nanomaterial provided in the present application can achieve dual-mode dynamic luminescence under the excitation of a 980nm diode laser / 365nm xenon lamp as an excitation light source, which is beneficial to improving the anti-counterfeiting level of anti-counterfeiting products.
[0101] In a dual-mode dynamic anti-counterfeiting luminescent nanomaterial provided in Example 1, the luminescent properties of UCNPs@SiO2 coated with silica, UCNPs@SiO2-Eu(TTA)3 coated with a down-conversion fluorescent complex, and UCNPs@SiO2-Eu(TTA)3-HYA and UCNPs@SiO2-Eu(TTA)3-HYA / CS combined with a polysaccharide functional layer are as follows: Figure 6 As shown in Figure a~b; Figure 6 From the upconversion luminescence spectrum shown in Figure a, it can be seen that after coating with silica, downconversion fluorescent complex Eu(TTA)3 and polysaccharide functional layer HYA / CS, the position and intensity of the emission peak of UCNPs-OA did not change, indicating that the silica coating modification can prevent the energy transfer between UCNPs and Eu(TTA)3, and successfully prepare the hybrid nanocomposite structure with interface energy regulation, and the polysaccharide functional layer HYA / CS will not adversely affect the luminescence performance of the dual-mode dynamic anti-counterfeiting luminescent nanomaterials; at the same time, Figure 6 As shown in the down-conversion luminescence spectrum in Figure b, it can be seen that the emission peak position and luminescence intensity of the down-conversion luminescence of UCNPs@SiO2-Eu(TTA)3 are similar to Figure 5 The down-conversion luminescence of Eu(TTA)3 in UCNPs@SiO2 is comparable, which shows that UCNPs@SiO2-Eu(TTA)3 has good down-conversion red light emission performance.
[0102] In a dual-mode dynamic anti-counterfeiting luminescent nanomaterial provided in Example 1, the up-conversion emission spectrum of UCNPs-OA (300K~500K) and the down-conversion emission spectrum of Eu(TTA)3 (77K~350K) are as follows: Figure 7 As shown in Figure a~b; Figure 7 From the upconversion luminescence spectrum shown in Figure a, it can be seen that in the range of 300K~500K, as the temperature increases, the upconversion emission intensity of UCNPs-OA increases (489nm, 543nm, 585nm, 620nm, 696nm) or decreases (449nm, 477nm, 646nm); Figure 7 It can be seen from the down-conversion luminescence spectrum shown in Figure b that in the range of 77K~350K, as the temperature rises, the down-conversion emission intensity of Eu(TTA)3 gradually decreases; this illustrates that the dual-mode dynamic anti-counterfeiting luminescent nanomaterial provided in the present application can not only achieve dual-mode dynamic luminescence when excited by a 980nm diode laser / 365nm xenon lamp as an excitation light source; the luminescence intensity can also change when the temperature changes, which is beneficial to further improve the anti-counterfeiting level of anti-counterfeiting products.
[0103] Experimental Example 3
[0104] Experimental Example 3 of the present application conducts a performance test on the dual-mode dynamic anti-counterfeiting luminescent nanomaterial provided in Example 1.
[0105] Among them, the instruments used in the performance test include a 980nm laser pen, a 365nm UV box and a dry thermostat.
[0106] The performance test process includes: first, centrifuging an appropriate amount of OA-UCNPs cyclohexane dispersion, drying and then pressing it into tablets to obtain UCNPs-OA tablets, grinding Eu(TTA)3 solid with potassium bromide and pressing it into tablets to obtain Eu(TTA)3 tablets; then using a dry thermostat to heat the UCNPs-OA tablets to 300K and 500K respectively, and then using a 980nm laser pen as an excitation light source for excitation, using a dry thermostat to heat the Eu(TTA)3 tablets to 300K and 350K respectively, and then using a 365nm ultraviolet light source as an excitation light source for excitation.
[0107] Performance test results such as Figure 8 As shown, from Figure 8 It can be seen that with the change of temperature, the intensity and color of the emitted fluorescence of the UCNPs-OA sheet change significantly. The higher the temperature, the weaker the purple light. The intensity of the emitted fluorescence of the Eu(TTA)3 sheet also changes significantly with temperature. The higher the temperature, the weaker the red light. This shows that the UCNPs-OA sheet and Eu(TTA)3 sheet provided in this application both have dynamic luminescence properties.
[0108] This experimental example further conducted an anti-counterfeiting performance test. In the anti-counterfeiting performance test, the dual-mode dynamic anti-counterfeiting luminescent nanomaterial provided in Example 1 was prepared as an anti-counterfeiting product.
[0109] The anti-counterfeiting performance test process includes: first, immersing the dragon-shaped pattern made of filter paper in the ethanol solution of UCNPs@SiO2-Eu(TTA)3 provided in Example 1 for 2 minutes, and then leaving it at room temperature for natural drying, so that the UCNPs@SiO2-Eu(TTA)3 provided in Example 1 is coated on the surface of the dragon-shaped filter paper product to obtain a UCNPs@SiO2-Eu(TTA)3 paper-based sample, and then exciting it with a 365nm ultraviolet light source and a 980nm laser pen at room temperature, 350K and 500K, respectively.
[0110] Anti-counterfeiting performance test results are as follows Fig. 9 As shown, from Fig. 9 It can be seen that when excited by a 365nm ultraviolet box as a light source, red light will be emitted; and when excited by a 980nm laser pen as a light source, purple light will be emitted; when the temperature rises from room temperature to 350K, the intensity of the down-converted red light and the up-converted purple light decreases; when the temperature continues to rise to 500K, the intensity of the down-converted red light and the up-converted purple light decreases significantly; therefore, the dragon-shaped filter paper product has a good anti-counterfeiting level.
[0111] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A dual-mode dynamic anti-counterfeiting luminescent nanomaterial, It is characterized in that From inside to outside, it includes: up-conversion fluorescent nanoparticles, silica coating layer, down-conversion fluorescent complex Eu(TTA) 3 Assembly layer; The up-conversion fluorescent nanoparticles include: core nanoparticles NaGdF 4 :Yb / Tm、NaYF 4 :Tb inner shell and NaYF 4 Outer shell layer.
2. A dual-mode dynamic anti-counterfeiting luminescent nanomaterial according to claim 1, It is characterized in that The core nanoparticle NaGdF of the upconversion fluorescent nanoparticle 4 :Yb / Tm, the molar ratio of Yb: Tm: Gd is 40~80:0.5~2:20~60, NaYF 4 In the Y:Tb inner shell, the molar ratio of Y:Tb is 70~95:5~30.
3. A dual-mode dynamic anti-counterfeiting luminescent nanomaterial according to claim 1, It is characterized in that The dual-mode dynamic anti-counterfeiting luminescent nanomaterial also includes a polysaccharide functionalized layer, which is bonded to the down-conversion fluorescent complex Eu(TTA) through electrostatic action. 3 Assemble the surface of the layer.
4. A dual-mode dynamic anti-counterfeiting luminescent nanomaterial according to claim 3, It is characterized in that The polysaccharide functionalized layer is selected from a hyaluronic acid functionalized layer and / or a chitosan functionalized layer.
5. A method for preparing a dual-mode dynamic anti-counterfeiting luminescent nanomaterial according to any one of claims 1 to 4, It is characterized in that Includes steps: Step S1: adding ammonium fluoride and sodium hydroxide to a precursor reaction solution containing a gadolinium / ytterbium / thulium-oleic acid complex to perform a core coprecipitation reaction to obtain core nanoparticles NaGdF 4 :Yb / Tm; Step S2: core nanoparticles NaGdF 4 :Yb / Tm, ammonium fluoride, and sodium hydroxide are added to the precursor reaction solution containing yttrium / terbium-oleic acid complex to carry out inner shell coprecipitation reaction to obtain core-shell nanoparticles NaGdF 4 :Yb / Tm@NaYF 4 :Tb; Step S3: NaGdF 4 :Yb / Tm@NaYF 4 :Tb, ammonium fluoride, and sodium hydroxide are added to the precursor reaction solution containing yttrium-oleic acid complex to carry out shell layer coprecipitation reaction to obtain upconversion fluorescent nanoparticles NaGdF 4 :Yb / Tm@NaYF 4 :Tb@NaYF 4 ; Step S4: using a microemulsion method to prepare a 4 :Yb / Tm@NaYF 4 :Tb@NaYF 4 The surface of UCNPs@SiO 2 ; Step S5: UCNPs@SiO 2 , europium salt, 2-thenoyltrifluoroacetone, and ammonia were coordinated in ethanol solution to form UCNPs@SiO 2 Surface coating of down-conversion fluorescent complex Eu(TTA) 3 Assemble the layers to obtain UCNPs@SiO 2 -Eu(TTA) 3 .
6. A method for preparing a dual-mode dynamic anti-counterfeiting luminescent nanomaterial according to claim 5, It is characterized in that After step S5, the method further includes the following steps: Step S6: Modify hyaluronic acid onto UCNPs@SiO 2 -Eu(TTA) 3 Surface, UCNPs@SiO 2 -Eu(TTA) 3 -HYA; Step S7: Modify chitosan onto UCNPs@SiO 2 -Eu(TTA) 3 -HYA surface, UCNPs@SiO 2 -Eu(TTA) 3 -HYA / CS.
7. The method for preparing a dual-mode dynamic anti-counterfeiting luminescent nanomaterial according to claim 5, It is characterized in that Step S5 specifically includes: Step S51, adding the ethanol solution of europium salt to UCNPs@SiO 2 UCNPs@SiO 2 -Eu; Step S52: adding 2-thenoyltrifluoroacetone ethanol solution and ammonia water to UCNPs@SiO 2 -Eu ethanol solution, and then the coordination reaction was carried out to obtain UCNPs@SiO 2 -Eu(TTA) 3 .
8. Application of a dual-mode dynamic anti-counterfeiting luminescent nanomaterial in the preparation of anti-counterfeiting products or information storage.
9. A safety ink, It is characterized in that The components include: a dual-mode dynamic anti-counterfeiting luminescent nanomaterial as described in any one of claims 1-4. 10.An anti-counterfeiting product, It is characterized in that A product comprising a dual-mode dynamic anti-counterfeiting luminescent nanomaterial as claimed in any one of claims 1 to 4; The dual-mode dynamic anti-counterfeiting luminescent nanomaterial covers the surface of the product.
